Dynamic analysis of a floating spherical buoy fastened by mooring cables. (15th July 2016) - Zhu, Xiangqian; Yoo, Wan Suk
Abstract: A numerical model is constructed for a floating spherical buoy fastened by mooring cables. Two cables are distributed on the two sides of the buoy with a symmetric layout. The tops of the cables are connected to the buoy, and the bottoms of the cables are fixed to the seabed. Dynamics of the cables and buoy are considered in the numerical model. The model of the buoy is created by a numerical integration algorithm, which is more efficient than the polyhedral mesh method. Both the hydrostatic and hydrodynamic loads are expressed on the connection point between the buoy and cables. The cable is divided into elements by the lumped mass model. The hydrodynamic loads are expressed with respect to an element-fixed frame generated by the vectors of the element orientation and the relative velocity of the fluid. A concise formulation of the hydrodynamic drag force is proposed with respect to the frame. The dynamic motions of the floating system are analyzed, and the relationships between these motions and the propagating waves are illustrated based on given layout of the mooring system. All of the simulation results are verified using a commercial simulation code ProteusDS. Highlights: Dynamics of the cables are considered in the analysis of the floating spherical buoy. A concise formulation of the hydrodynamic drag force is proposed based on a new element frame. The model of the spherical buoy is generated efficiently using a numerical integration algorithm. Effects of the propagating waves on the mooring systems are illustrated.